Editorial: Moving forward with mobile positioning data in academic research - Acker, Veronique van; Neutens, Tijs (European Journal of Transport and Infrastructure Research, 2015)
This special issue of the European Journal of Transport and Infrastructure Research (EJTIR) comprises three papers addressing some key issues in transport geographical research that use location tracking data. Preliminary versions of those papers were presented at the Mobile Ghent 2013 Conference. This event is part of a series of biannually held conferences on location-based services (LBS) that initially started in Tartu, Estonia. This editorial briefly points to the growing academic relevance of mobile phone tracking data and location-based services, describes the history and aim of the Mobile Ghent conference and gives a preview of the selected contributions.